Meningkatkan Kemampuan Speaking Siswa Kelas XII TAV SMKN 2 Kota Bima Dengan Model Pembelajaran Kooperatif Tipe Jigsaw - Hidayat, Hidayat (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This research is aimed to know (1) the increasing of speaking achievement of class XII TAV SMKN 2 Kota Bima by using cooperative learning type jigsaw (2) to know the students’ responses towards the using of cooperative learning type jigsaw in learning speaking. The data collecting; observation, students’ responses of the questionnaire and the result of the scores from sycle 1 and sycle 2. The technique of analyzing data is descriptive analysis; to analyze the response of the questionnaire and students’ score from sycle 1 (one) and sycle 2(two). The result of the research is showed that the using of cooperative learning type jigsaw  can increase the speaking ability of students class XII TAV SMKN 2 Kota Bima in academic year 2020/2021.  The result of the sycle 2 (two); students’ score is 75,32. It means that as stated by Nana Sujana (2009: 62), if the score is 75 means success. The result of the questionnaire; number 1(one) is 92 % yes;  question number 2(two)  12% is yes for negative statement; question number 3 (Three) 80%   is yes; question number 4 (four) 88% is yes; and question number 5 (five) that 96% students answered yes. The hypothesis which is stated that the using cooperative learning type jigsaw can increase students ability in speaking of students class XII TAV SMKN 2 Kota Bima is accepted.